2023
DOI: 10.3390/toxins15070474
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Investigation of Unexpected Helicoverpa zea (Boddie) Survival and Ear Injury on a Transgenic Maize Hybrid Expressing Cry1A/Cry2A/Vip3A Toxins

Abstract: The wide occurrence of resistance to Cry1A and Cry2A insecticidal toxins from Bacillus thuringiensis (Bt) in the corn earworm/bollworm Helicoverpa zea (Boddie) leaves the Vip3A toxin produced during the vegetative stage of Bt as the only fully active toxin expressed in transgenic crops to control H. zea in the U.S.A. During 2021, the first unexpected survival of H. zea and injury (UXI) on a maize hybrid expressing Cry1A.105, Cry2Ab2, and Vip3Aa in Louisiana, U.S.A. were observed in two sentinel plots used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…More studies may be needed to understand the genetic changes in FAW susceptibility to Vip3Aa/Cry insecticidal proteins and help inform decision making for resistance management [32,43,45]. FAW population pressure on host crops is likely influenced by the genetic background of field populations and their environmental factors, including climatic variables, native or transgenic plant resistance traits, and pest and crop management practices [3,20,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…More studies may be needed to understand the genetic changes in FAW susceptibility to Vip3Aa/Cry insecticidal proteins and help inform decision making for resistance management [32,43,45]. FAW population pressure on host crops is likely influenced by the genetic background of field populations and their environmental factors, including climatic variables, native or transgenic plant resistance traits, and pest and crop management practices [3,20,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…By 2016, resistance to Cry1 toxins had become common throughout the US and Cry2 resistance was emerging (Dively et al 2016; Reisig et al 2018). Recent studies concluded that resistance to Cry2Ab2 has become common, and that selection was ongoing as of 2019 (Yu et al 2021; Huang et al 2023). The genetic basis of Bt resistance is known to be complex and likely arose from standing variation, with unique genetic architectures underlying resistance to different Cry toxins (Taylor et al 2021; Benowitz et al 2022).…”
Section: Introductionmentioning
confidence: 99%